62(30x-80)-43(52-20x)=377

Simple and best practice solution for 62(30x-80)-43(52-20x)=377 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 62(30x-80)-43(52-20x)=377 equation:


Simplifying
62(30x + -80) + -43(52 + -20x) = 377

Reorder the terms:
62(-80 + 30x) + -43(52 + -20x) = 377
(-80 * 62 + 30x * 62) + -43(52 + -20x) = 377
(-4960 + 1860x) + -43(52 + -20x) = 377
-4960 + 1860x + (52 * -43 + -20x * -43) = 377
-4960 + 1860x + (-2236 + 860x) = 377

Reorder the terms:
-4960 + -2236 + 1860x + 860x = 377

Combine like terms: -4960 + -2236 = -7196
-7196 + 1860x + 860x = 377

Combine like terms: 1860x + 860x = 2720x
-7196 + 2720x = 377

Solving
-7196 + 2720x = 377

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7196' to each side of the equation.
-7196 + 7196 + 2720x = 377 + 7196

Combine like terms: -7196 + 7196 = 0
0 + 2720x = 377 + 7196
2720x = 377 + 7196

Combine like terms: 377 + 7196 = 7573
2720x = 7573

Divide each side by '2720'.
x = 2.784191176

Simplifying
x = 2.784191176

See similar equations:

| -2k=1/4 | | x-14=5x+18 | | 4732-500=x | | 12x+5=11(x+7)+10 | | 7x-1=x-1+6x | | 2m-6=-1+m-4m | | 4(2x+10)=16 | | -1/2(3x-5)=7 | | -t^3-6t^2+12t+50=0 | | 5(x-5)-12=23x-127 | | x^2-2x+8=-12+7x | | 9h=-39 | | 3x+5=90 | | 15=4*3.14*r | | 24x^2-4x-8= | | 4(6x+18)=120 | | 24x^2+4x-8= | | 10x+1=x-8+6x | | 6(x-7)-12=20x-222 | | 3.3d-7.2=0.8d+7.3 | | (12)-24=x | | 6(x-4)=6(x-1) | | 15=4(3.14)r | | 12*-24= | | 5n-5=-6n-16 | | a/15+4/15=9/5 | | 5(x-4)+4x=9x-20 | | 6x-2.6666666=6x | | -6(x+8)+365=11+18 | | a(x+c)=2ad+c | | 4x^2-6x+3= | | -3(x+9)+97=32+11 |

Equations solver categories